Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content 1. The role of strategic thinking in achieving government innovation: A filed study on employees of the Ministry of Justice in Jeddah Mrs. Seham Sharaf Alzhrani, Co-Prof. Faisal Ahmad Shuaibi 2. The impact of implementing the health transformation strategy on service delivery from the employees’ point of view in KSA Mr. Hassan Amer Al-Shehri 3. The impact of empowerment of women leaders on job performance: An empirical study on the government sector in KSA Co-Prof. Hossam Hassan Sharawi, Ms. Amani Saleh Al-Said 4. The Use of Information Technology and its Impact on The Efficiency of Modern Management Accounting Methods in Jordanian Government Institutions in the Time Period 2022-2023 Mr. Majdi Mohammad Ahmad Almalkawi 5. The effectiveness of procedures followed by organizers during Hajj season on the safety of the elderly in Al-Mashaer train area Mrs. Lina Mohammed Alsulimani 6. Factors affecting the quality of internal audit reports in Jordanian ministries and government institutions Mr. Malik Hussein Ahmad Almalkawi 7. Modern digitization and its expected impact on the efficiency of Islamic financial transactions in Libya Mrs. Hamida Abdel Aziz Ali Islio, Dr. Muhammad Ahmed Ali Dabou 8. Modern methods of the crime of terrorism in domestic and international laws Lecturer Amnah Mulfi Alsulami